Implicit Prices of Sustainability on the German Online Market for Honey - Katharina Bissinger; Roland Herrmann; Lisa Krandick (German Journal of Agricultural Economics (GJAE), 2019)
Sustainability characteristics play an increasing role in food markets. At least some consumers are willing to pay a price for organic or regional production, animal welfare or fairtrade. In order to analyse implicit prices of sustainability characteristics, it is important to go beyond consumer studies as such characteristics affect marginal costs as well. We employ a hedonic price analysis to compare the price premium of very different sustainability characteristics on the German online market for honey. Honey is particularly interesting, because it is perceived as a natural product, and regional and organic production competes with, for example, fairtrade products from developing countries. Consumer prices for honey contain positive as well as negative implicit prices for sustainability characteristics. Apparently, consumer valuation in terms of the marginal willingness to pay and marginal costs differ strongly across the sustainability
Keywords: 330